Development of a Mathematical Model for the Optimization of Natural Resources in Villages - Ikhsan Faturohman; Yugi Hilmi (UIN Sumatera Utara, 2025)
This study integrates Linear Programming (LP) and Geographic Information System (GIS) to optimize land and water resource utilization in Indonesian rural areas. The proposed multi-period LP model aims to maximize farmers' net profit under land, water, and labor constraints, where decision variables represent the land area (in tumbak) allocated to each crop per period. Conducted in three agricultural villages of Garut Regency with 60 farmer respondents selected through stratified sampling, the model was solved using Excel Solver and spatially visualized through GIS. Results show an optimal cultivated area of 453.202 tumbak, utilizing 16,412.49 m³ of water and 5,319.098 man-days of labor, producing Rp 2,078,047,500 in gross revenue and Rp 26,493,556 in net profit. Land-use efficiency improved by 64.8% from baseline conditions, with land as the main binding constraint. The model offers a practical decision-support tool for policymakers to plan crop rotation, irrigation scheduling, and sustainable land-use strategies.